If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3(6 + -2c) = 27 3x + (6 * -3 + -2c * -3) = 27 3x + (-18 + 6c) = 27 Reorder the terms: -18 + 6c + 3x = 27 Solving -18 + 6c + 3x = 27 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 6c + 18 + 3x = 27 + 18 Reorder the terms: -18 + 18 + 6c + 3x = 27 + 18 Combine like terms: -18 + 18 = 0 0 + 6c + 3x = 27 + 18 6c + 3x = 27 + 18 Combine like terms: 27 + 18 = 45 6c + 3x = 45 Add '-3x' to each side of the equation. 6c + 3x + -3x = 45 + -3x Combine like terms: 3x + -3x = 0 6c + 0 = 45 + -3x 6c = 45 + -3x Divide each side by '6'. c = 7.5 + -0.5x Simplifying c = 7.5 + -0.5x
| -2(-3x+3)=-24 | | -5x+6x-10=-5 | | 10x-x+1=44 | | 15/2m+7/3=59/6 | | 2x=25-x | | 7(2x+9)=7 | | h+47=63 | | (-10)-(-12)= | | 3t^2-7+-20=0 | | 6/11p+2=3p-8 | | (-11)+10= | | 34=2+n | | 3z-x=46 | | x^2+40=-14x | | -3(7+7x)=-42 | | x^2-16x=-39 | | 30=12x+8x-5x | | x^2+22x=-121 | | 8x+6x=36 | | 3n+14=30 | | 5(10+3x)=200 | | 56=7+m | | 2x+7.5=4x+3 | | P=-x^2+105x-1050 | | 15b-3a=60 | | 8r^2-24=0 | | -1/2(4a+2)=5 | | 3x+20=-8 | | 16r=176 | | -24+x=-35 | | 123=k+32 | | 4(10+6x)=328 |